2021
DOI: 10.3390/ijerph18084301
|View full text |Cite
|
Sign up to set email alerts
|

Structural Equation Model of Elementary School Students’ Quality of Life Related to Smart Devices Usage Based on PRECEDE Model

Abstract: Korean elementary school students have the lowest life satisfaction levels among OECD countries. The use of smart devices has led to smartphone addiction, which seriously affects their quality of life. This study aims to establish and test variables that affect the quality of life (QOL) of elementary school students based on the Predisposing, Reinforcing and Enabling Constructs in Educational Diagnosis and Evaluation (PRECEDE) model, using smart device-related parental intervention, self-efficacy, social suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Additionally, media addiction-related external problems are also reflected in sensation-seeking and rule-breaking behavior (Choi et al, 2021). Both internal and external behavioral problems and screen time, in general, are associated with social and academic adaptation, which consequently both affect school adaptation (Ahn et al, 2017;Choi et al, 2021;Lee and Lee, 2021;Lee and Park, 2022). Consequently, poor school adaptation can negatively impact academic and social aspects, further exacerbating the problem and creating a loop.…”
Section: Effect Of Digital Interaction Towards Wellbeingmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, media addiction-related external problems are also reflected in sensation-seeking and rule-breaking behavior (Choi et al, 2021). Both internal and external behavioral problems and screen time, in general, are associated with social and academic adaptation, which consequently both affect school adaptation (Ahn et al, 2017;Choi et al, 2021;Lee and Lee, 2021;Lee and Park, 2022). Consequently, poor school adaptation can negatively impact academic and social aspects, further exacerbating the problem and creating a loop.…”
Section: Effect Of Digital Interaction Towards Wellbeingmentioning
confidence: 99%
“…Digital addiction can also indirectly cause additional health problems such as lack of sleep and reduced sleep quality leading to various health problems Park et al, 2022;Yoon et al, 2021). Additionally, smartphone and media addiction tend to be harmful to overall health as it can lower health-promoting behavior due to low self-regulation abilities (Lee and Lee, 2021). Hence, unhealthy and unregulated use of digital devices affect QOL as a whole, including physical, emotional, social, and academic areas.…”
Section: Effect Of Digital Interaction Towards Wellbeingmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, previous studies have shown that the increasing use of digital devices has raised concerns regarding physical and psychological health problems, and even quality of life [ 16 ]. In addition, this increase may lead to digital media addiction.…”
Section: Introductionmentioning
confidence: 99%